(18)F-fluorodeoxyglucose positron emission tomography/computed tomography imaging review of benign lesions of the thorax - Ravikanth, Reddy (World J Nucl Med, 2020)
2-deoxy-2-(Fluorine-18) fluoro-D-glucose ((18)F-FDG) positron emission tomography/computed tomography (PET/CT) has been used exclusively to diagnose malignancies. However, increased (18)F-FDG uptake is not always limited to malignant lesions. This imaging review demonstrates the physiological (18)F-FDG uptake of normal structures in the thorax and illustrates many benign pathological lesions with standardized uptake value >2.5. These various conditions can be broadly categorized into three groups: infective lesions, active granulomatous diseases such as sarcoidosis, noninfectious/inflammatory, or proliferative conditions such as radiation pneumonitis, postlung transplant lymphoproliferative disorders, occupational pleuropulmonary complications, and postsurgical conditions, all of which can demonstrate varying degrees of (18)F-FDG uptake on PET/CT based upon the degree of inflammatory activity. Familiarity of false-positive findings improves the PET/CT evaluation accuracy of benign lesions of the thorax. Radiation exposure and surgical history correlation along with imaging cross check evaluation of radiographs and magnetic resonance images for the anatomic location remains the mainstay of PET/CT characterization of positive findings.